Answer:
53 degrees
Step-by-step explanation:
Since we don't know the measure of the radius
UZ =127
UX=127
ZX =154
360-154= 106
106/2=53
XY=53
YZ=53
y equals 3/8 x+ 12 write the equation in standard form using integers
Answer:
-3x + 8y - 96 = 0
Step-by-step explanation:
Standard form is ax + by + c = 0.
Converting from standard to slope-intercept form:
ax + by + c = 0
by = -ax - c
y = -a/b x - c/b
Compare the conversion formula to y = 3/8 x + 12.
In the equation, the slope is 3/8, which is the result of -a/b.
a= -3 and b=8
In the equation, 12 is a result of -c/b.
If b is 8:
-c/b = 12
-c/8 = 12
-c = 96
c = -96
Test a= -3 and b=8 and c= -96 in standard form converts to y=3/8 x+ 12
ax + by + c = 0
-3x + 8y - 96 = 0
-3x + 8y = 96
8y = 3x + 96
y = 3/8 x + 96/8
y = 3/8 x +12
This is correct. Therefore a= -3, b=8 and c= -96.
The standard form is -3x + 8y - 96 = 0
PLEASE HELP DUE TONIGHT!!!!!in the number that should go in the blank. Use a slash (/) to show a fraction.
Abigail bought 3/4 of a pound of hard candy. She has 3/8 of a pound of candy left, so she has eaten Answer
pound of candy.
Abigail has eaten 3/8 of a pound of candy.
This is the answer because 3/4 is equivalent to 6/8, and if Abigail has eaten 3/8 of a pound of that 6/8 pound of candy, then there will be 3/8 remaining (6/8 - 3/8 = 3/8).
To find out how much candy Abigail has eaten, we subtract the amount of candy she has left (3/8 of a pound) from the original amount she bought (3/4 of a pound). The calculation shows that Abigail has eaten 3/8 of a pound of candy.
The student is asking how much candy Abigail has eaten if she originally bought 3/4 of a pound and now has 3/8 of a pound left. To calculate the amount of candy eaten, we subtract the amount left from the original amount. Since we are working with fractions, we ensure the denominators are the same before subtracting.
The steps to solve the problem are as follows:
Original amount of candy: 3/4 pound
Amount left: 3/8 pound
Calculate how much has been eaten: (3/4) - (3/8)
Convert the first fraction to have a denominator of 8: (6/8) - (3/8)
Subtract the second fraction from the first: (6/8) - (3/8) = 3/8
Abigail has eaten 3/8 of a pound of candy.
? ÷ 5 = 6 solve an equation
Answer: 30
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
you do 5x6 and that gives you 30 and then to double check your answer you do 5 divided by 30 :)
d=rt when r=35 mi/h and t= 2 h
Answer:
The distance, D for the given expression is 70 miles
Step-by-step explanation:
Given as :
D = r t
r = 35 mi/ h
t = 2 h
Now, According to question
Distance = speed × Time
Where speed = r
Time = t
Distance = D
Now, from question
D = 35 miles per hour × 2 hours
So, D = 70 miles
Hence The distance, D for the given expression is 70 miles . answer
2 sin^2 theta + 3 cos theta = 3
Answer:
θ = ±π/3 + 2kπ
θ = 0 + 2kπ
Step-by-step explanation:
2 sin² θ + 3 cos θ = 3
Use Pythagorean identity:
2 (1 − cos² θ) + 3 cos θ = 3
2 − 2 cos² θ + 3 cos θ = 3
0 = 2 cos² θ − 3 cos θ + 1
Factor:
0 = (2 cos θ − 1) (cos θ − 1)
cos θ = 1/2
θ = ±π/3 + 2kπ
cos θ = 1
θ = 0 + 2kπ
Evaluate [tex]\frac{d}{2}[/tex] + [tex]\frac{c}{3}[/tex] for c = 6 and d = 10.
A. 6
B. [tex]\frac{16}{5}[/tex]
C. 7
D. 10
Answer:
C) 7
Step-by-step explanation:
10/2=5
6/3=2
---------
5+2=7
Challenger Elementary School has 800 students. Every Wednesday, 12 percent of the students stay after school for Chess Club. How many students attend Chess Club on Wednesdays?
Answer: help me on my question
Step-by-step explanation:write the answer then submit it and thanks tou
A group of 4 friends shares 2 packs of gum equally. There are 8 pieces of gum in
each pack. Which set of equations shows how many pieces of gum, g, each
friend receives?
2 x 8 = 16
16 x 4 = g
2 x 8 = 16
16 : 4 = g
4 x 2 = 8
8:8=g
4 x 2 = 8
8 x 8 = g
Done →
Answer:
Each friend receives 4 pieces of gum. The answer is B).
Step-by-step explanation:
2 packs of gum=2*8=16 pieces of gum in total,
16/4=4
The correct answer is 4 gums
⇒each pack of gums contains 8 gums.
⇒there are 2 packs of gums
⇒total number of gums is 8×2=16
∴ each friend receives [tex]\frac{16}{4}[/tex]=4
so; g=4
What is the formula of the unitary method?
The formula of the unitary method is to find the value of a single unit and then multiply the value of a single unit by the number of units to get the necessary value
Learn more about the unitary method here:https://brainly.com/question/917963
#SPJ2
Northwest molded mold plastic handles which cost 0.20 per handle to mold. The fixed cost to run the molding machine is $ 7396 per week. If the company sells the handles for $4.20 each, how many handles must be molded and sold weekly to break even?
Answer:
1849 handles
Step-by-step explanation:
Break Even is the point when costs = profit
Since each handle takes $0.20 to make (cost) and they sell it for ($4.20), the profit from each handle is:
Profit = 4.20 - 0.20 = $4
The weekly costs are $7396. Break even would mean to gain this amount from selling handles (profit).
So, from each handle, we get $4 and to make $7396, we would need:
7396/4 = 1849 handles
The digits of a two-digit number sum to 8. When the digits are reversed the resulting number is 18 less than the onginal
number. What is the original number?
Answer:
53
Step-by-step explanation:
Given: The sum of two digit number is 8
Reversing the digit will get us number 18 less than the original.
Lets take x as tenth digit of our number and y as unit digit of our number.
As given sum of digit is 8
∴ [tex]x+y= 8[/tex]
∴ [tex]y= 8-x[/tex] - equation 1
We also know that reversing the digit will get us number 18 less than the original.
∴ [tex]10y+x = 10x +y-18[/tex]
Now, lets put the value of y from equation 1
⇒ [tex]10(8-x) + x = 10x+ (8-x)- 18[/tex]
⇒ [tex]80-9x= 9x-10[/tex]
⇒ [tex]90= 18x[/tex]
∴ [tex]x= 5[/tex]
Next, substituting the value of x in equation 1
[tex]y= 8-x[/tex]
⇒ [tex]y= 8-5 = 3[/tex]
∴ [tex]y= 3[/tex]
∴ The original number is 53, sum of the digit is 8 and if we reverse the digit of the number, we get 35, which is 18 less than the original number.
The sum of two numbers is 138 one number is 20 less than the other find the numbers
Answer:
The answer is 59 & 79
Step-by-step explanation:
59+79=138
79-20=59
59+20=79
prism M and pyramid n have the same base area and the same height. cylinder p and prism Q have the same height and the same base perimeter. cone z has the same base area as cylinder y but its height is 3 times the height of cylinder y the figures_ and _ have the same volume
Answer:
The volume of cone z has the same base area as cylinder y but its height is 3 times the height of cylinder y have the same volume.
Step-by-step explanation:
The volume of a cylinder having base area 'A' and height 'H' is given by V = AH, and the volume of a cone having the same base area as the cylinder i.e. A and height 3 times the height of the cylinder i.e. 3H is given by [tex]V' = \frac{1}{3} A(3H) = AH[/tex].
So, V = V'
Hence, the volume of cone z has the same base area as cylinder y but its height is 3 times the height of cylinder y have the same volume. (Answer)
Can someone help me on 1, 2, 3 and 4 plz I really need help
Answer:
NO
YES
NO
NO
Step-by-step explanation:
For a number to be the solution of the equation, the number should satisfy it.
To check if t satisfies, plug the number and compare LHS and RHS.
1) 3z + 4 = 15
Substituting z = -5, we get 3(-5) + 4 = -15 + 4 = -11 [tex]$ \ne $[/tex] 15.
Therefore, -5 is not the solution of the equation.
2) 8 - [tex]$ \frac{x}{2} $[/tex] = 0
Substituting x = 16, we get 8 - [tex]$ \frac{16}{2} = 8$[/tex]
⇒ 8 - 8 = 0
Therefore, 16 is a solution of the equation.
3) 4(p + 5) = 60
Substitute p = 12. 4(12 + 5) = 4(17) [tex]$ \ne $[/tex] 60.
Not a solution.
4) 8 - k = -48
If k = -40, then 8 - (-40) = 48
On the RHS we have -48. Not equal. So, it is not a solution.
What is the answer to this equation? (picture attached)
Answer:
x = [tex]\frac{42}{5}[/tex]
Step-by-step explanation:
Given
19 - [tex]\frac{5x+6}{4}[/tex] = 7 ( subtract 19 from both sides )
- [tex]\frac{5x+6}{4}[/tex] = - 12
Multiply both sides by - 4 to clear the fraction and the negative signs
5x + 6 = 48 ( subtract 6 from both sides )
5x = 42 ( divide both sides by 5 )
x = [tex]\frac{42}{5}[/tex]
how do you re-write 0.7 repeating as a simplified fraction?
Answer:
7/10
Step-by-step explanation:
because .7*10 = 70 and it would be 70/100 so you simplify it to 7/10
Answer:
[tex]\frac{7}{9}[/tex]
Step-by-step explanation:
Given
0.77......
We require 2 equations with the repeating part after the decimal point.
let x = 0.77.... (1) ← multiply both sides by 10
10x = 7.77.... (2)
Subtract (1) from (2) thus eliminating the repeating decimal
9x = 7 ( divide both sides by 9 )
x = [tex]\frac{7}{9}[/tex]
Can anyone help me solve this Algebra 2 Problem, i literally cant figure it out
Answer:
Zeros : 1 , -1, 3
Degree : 4
End Behaviour : At x-> ∞ f(x) -> ∞ and x->-∞ f(x) -> ∞
Y - intercept : -3
Extra Points: (0,-3), (2,-3)
Step-by-step explanation:
f(x) = 0 to find the zeros
[tex]Therefore (x+1)(x-1)^{2} (x-3) = 0[/tex]
Clearly x = -1,1,3
Here 1 is a repeating root as it is (x-1)²
Degree is highest power of x in f(x)
Clearly it is x*x²*x = x⁴ is the maximum power of x
Thus degree is 4
Looking at end behavior we substitute x->∞ and x-> -∞
Clearly f(x)>0 as all terms are positive and f(x)->∞
Similarly when x->-∞
f(x)>0 as 2 terms are -ve and their product is positive thus f(x)-> ∞
Y-Intercept is f(0)
f(0) = (0+1)(0-1)²(0-3) = 1*1*-3 = -3
Thus Y-Intercept is -3
Substitute x = 0 , 2 for extra points
Thus f(0) = -3
and f(2) = -3
Thus points on the graph (0,-3), (0,2)
We can use all this information to draw a graph remember that 1 is a repeating root so that will be a point of minima. The graph is a parabola that passes through x-axis at x = -1, 3.
Identify the standard form of a circle equation x^2+2x+y^2-2y=2
Answer:
The standard from of the expression is: [tex](x +1)^2 + (y-1)^2 = (2)^2[/tex]
Step-by-step explanation:
Here the given expression is :
[tex]x^2+2x+y^2-2y=2[/tex]
Now, the standard form of a circle is given as :
[tex](x-h)^2 + (y -k)^2 = r^2[/tex]
Here, (h,k) = Coordinates of Center, r = Radius
Also, use the algebraic identity:
[tex](a \pm b)^2 = a^2 + b^2 \pm 2ab\\[/tex]
Now, converting the given expression in the standard form, we get:
[tex]x^2+2x+y^2-2y=2[/tex]
Add 2 on both sides of the equation, we get:
[tex]x^2+2x+y^2-2y +2=2 + 2\\\implies x^2+2x + 1 + y^2-2y + 1 = 4\\\implies (x^2+2x + 1 )+ (y^2-2y + 1) = 4\\\implies (x +1)^2 + (y-1)^2 = (2)^2[/tex]
So, here the standard from of the expression is:
[tex](x +1)^2 + (y-1)^2 = (2)^2[/tex]
Center coordinates here are (h,k) = ( -1 ,1) and Radius = 2 units
The table below shows the numbers of tickets sold at a movie theater on Friday.
NUMBER OF TICKETS SOLD
Day
Adult Tickets
Children's
Tickets
1,678
976
Friday
Saturday
The number of each type of ticket sold on Saturday is described below.
• Adult tickets—2 times as many as the number of adult tickets sold
on Friday
• Children's tickets-3 times as many as the number of children's
tickets sold on Friday
Complete the table above to show the numbers of tickets sold on Saturday.
What is the total number of tickets sold over these two days?
The total number of tickets sold over these two days is 9,640.
Let's complete the table for Saturday:
For Saturday:
Adult Tickets: [tex]\(2 \times \text{Number of Adult Tickets on Friday}\)[/tex]
Children's Tickets: [tex]\(3 \times \text{Number of Children's Tickets on Friday}\)[/tex]
Using the information from Friday's sales:
Adult Tickets on Saturday: [tex]\(2 \times 976 = 1952\)[/tex]
Children's Tickets on Saturday: [tex]\(3 \times 1678 = 5034\)[/tex]
Now, we can complete the table:
[tex]\begin{array}{ccc}\text { Day } & \text { Adult Tickets } & \text { Children's Tickets } \\\text { Friday } & 976 & 1,678 \\\text { Saturday } & 1,952 & 5,034\end{array}[/tex]
To find the total number of tickets sold over these two days, add the tickets for Friday and Saturday:
Total Tickets Sold = Adult Tickets on Friday + Children's Tickets on Friday + Adult Tickets on Saturday + Children's Tickets on Saturday
[tex]\[ \text{Total Tickets Sold} = 976 + 1,678 + 1,952 + 5,034 \][/tex]
[tex]\[ \text{Total Tickets Sold} = 9,640 \][/tex]
Maria says if I multiply the current temperature by 4 and then subtract 40 the results is the same as 3 times the current temperature Richard says the current temperature is 20 degrees is Richard correct
Answer:
No, Richard is incorrect, the current temperature is 40 degrees.
Step-by-step explanation:
4x-40=3x
4x-3x=40
x=40
4/7 = 7/x solve for x
Answer:
x=49/4
Step-by-step explanation:
4/7=7/x
cross product
7*7=4*x
49=4x
x=49/4
If Jamie wants to maintain the relationship of black
beads to red beads, could she make a bracelet with
5 red beads? Explain your answer.
How would I get an answer??
Answer:for every five red beeds their are 5 black beeds
Step-by-step explanation:
To maintain the relationship of black beads to red beads, we need to know the ratio of black beads to red beads in the existing bracelet or the desired ratio. If the ratio is 1:1, for example, then you would need to use an equal number of black and red beads.
However, based on the information provided, it's not clear what the current or desired ratio is. If Jamie wants to maintain a specific ratio, you need to know that ratio.
For example, if the ratio is 2:1 (2 black beads for every 1 red bead), and you want to use 5 red beads, you would need 5×2=10 black beads to maintain the 2:1 ratio.
Without more information on the desired or existing ratio, it's not possible to determine whether using 5 red beads alone would maintain the relationship of black beads to red beads.
complete step by step
To maintain the relationship of black beads to red beads in a bracelet, we need to understand the existing ratio and then apply it to the new situation.
Let's say the current ratio of black beads to red beads in Jamie's bracelet is 3:2. This means that for every 3 black beads, there are 2 red beads.
Now, Jamie wants to make a bracelet with 5 red beads. To maintain the same ratio, we need to determine the corresponding number of black beads.
The ratio of black beads to red beads is 3:2, which simplifies3x:2x for some positive value of x.
Since Jamie wants 5 red beads, we set up the equation: 2x-5
Now, solve for x:
x- 5/2
Now that we know the value of x, we can find the number of black beads:
Number of black beads - 3x-3 x (5/2) - (15/2) - 7.5
However, since the number of beads must be a whole number, we need to adjust. In this case, Jamie cannot make a bracelet with exactly 5 red beads while maintaining the ratio of 3:2. She would need to choose a different number of red beads that allows for a whole number of black beads according to the established ratio.
In conclusion, to maintain the relationship of black beads to red beads, Jamie cannot make a bracelet with exactly 5 red beads. The number of red beads chosen must allow for a whole number of black beads based on the given ratio.
**URGENT:** It will take Mr. Warner 15 1/2 hours to install a fence. Each day, he works 1 1/3 hours on the fence. After he finished working on the fence yesterday, he had 3 1/2 hours left to do. For how many days has Mr. Warner worked on the fence?
Which set of ordered pairs is a function?
A. (1,2) (3,4) (5,6) (3,-4)
B. (8,4) (4,3) (2,2) (8,1)
C. (2,5) (3,10) (4,15) (5,20)
D. (2,4) (2,3) (2,1) (2,0)
Answer:
OPTION C
Step-by-step explanation:
An element in the domain should be mapped to exactly one element on the co-domain. Also, every element in the domain should be mapped to an element in the co-domain.
These two conditions are satisfied to call a relation, a function.
Two different elements in the domain can be mapped to the same element in the co-domain. But the same element in the domain cannot be mapped to two different elements in the co-domain.
A) (1,2), (3,4), (5,6), (3,-4)
Here, the element '3' is mapped to 4 and -4. So, this is not a function.
B) (8,4), (4,3), (2,2), (8,1)
'8' is mapped to 4 and 1. So, it is not a function.
C) (2,5), (3,10), (4,15), (5,20)
All the elements in the domain are mapped to an element in the co-domain. Also, every element in the domain has exactly one image in the co-domain. So, this relation is a function.
D) (2,4), (2,3), (2,1), (2,0)
The element '2' has more than one image. Clearly, it contradicts the definition of a function.
So, only OPTION C is the answer.
Choose the property of addition that justifies the equation.
(6 + x) + 8 = 6 + (x + 8)
(Choose one)
Answer:
Associative
Step-by-step explanation:
Associative property is the one that says that when 3 or more numbers are summed, the grouping of such numbers has no effect on the result of the sum. It is:
(a + b) + c = a + (b + c) for every a, b and c real numbers.
5. Mike weighs 200 pounds and plans to
lose 1.5 pounds a week. Jeff weighs 180
pounds and plans to lose 0.5 pounds a
week. When will Mike and Jeff weigh the
same?
Answer:
20 weeks
Step-by-step explanation:
200-1.5x=180-.5x
20=1x
X=20
$75 dinner; 18% tip
please help me!
Answer:
88
Step-by-step explanation:
Answer:
$13.50
Step-by-step explanation:
So your total would be $88.50
Factor completely x2 - 16y2
Answer:
(x+4y)(x-4y)
Step-by-step explanation:
Since
[tex]\large a^2-b^2=(a+b)(a-b)[/tex]
we can see that
[tex]\large x^2-16y^2=(x+4y)(x-4y)[/tex]
Which graph represents the function over the interval [−3,3] ?
f(x)=⌈x+1⌉
Answer: The correct graph is the bottom left graph.
Step-by-step explanation:
Given function is f(x)=ceil(x+1)
To plot graph of f(x) in interval of(-3,3) :
ceil(x+1) is ceiling function
The output of ceil(x) is least integer greater than x
for example ceil(5.5)=6
For an interval of (-3,-2):
Take x=(-2.4)
x+1=(-1.4)
y=f(x)=ceil(x+1)=(-1)
Similarly,
For an interval of (-2,-1):
Take x=(-1.4)
x+1=(-0.4)
y=f(x)=ceil(x+1)=(0)
For an interval of (-1,0)
y=f(x)=1
For an interval of (0,1)
y=f(x)=2
For an interval of (1,2)
y=f(x)=3
For an interval of (2,3)
y=f(x)=4
Thus, The correct graph is the bottom left graph.
Answer:
The bottom left graph
Step-by-step explanation:
I took this quiz
3 When Klorina swims with the current, she swims 10 km
In 2 h. Against the current, she can swim only 8 km in
the same time. How fast can Klorina swim in still water?
What is the rate of the current?
Speed in still water [tex]=[/tex] 9km
Speed of the current [tex]=[/tex] 1 km
Answer:
Step-by-step explanation:
Speed of the current [tex]=[/tex] C
Speed of the still water [tex]=[/tex] S
Speed with the current [tex]=[/tex] [tex]([/tex] speed of the still water ₊ speed of the current [tex])[/tex]
[tex]=[/tex] S ₊ C
Speed with the current [tex]=[/tex] S ₊ C [tex]=[/tex] 10km
Speed against the current [tex]=[/tex] [tex]([/tex] speed of the still water ₋speed of the current [tex])[/tex]
[tex]=[/tex] S ₋ C
Speed against the current [tex]=[/tex] S ₋ C [tex]=[/tex] 8km
Speed in still water [tex]=[/tex] Speed with the current ₊ Speed against the current[tex])[/tex]÷ 2
[tex]= ([/tex] 10 ₊ 8 [tex])[/tex] ÷ 2
[tex]=[/tex] [tex]([/tex] 18 [tex])[/tex] ÷ 2
Speed in still water [tex]=[/tex] 9km
Speed of the current [tex]= ([/tex] Speed with the current ₋ Speed against the current[tex])[/tex] ÷ 2
[tex]= ([/tex] 10 ₋ 8 [tex])[/tex] ÷ 2
[tex]=[/tex] [tex]([/tex] 2 [tex])[/tex] ÷ 2
Speed of the current [tex]=[/tex] 1 km
An item is regularly priced at $55. It is now priced at a discount of 25 off the regular price.
Use the ALEKS calculator to find the price now.
Step-by-step explanation:
Do 25% of $55 which is $13.75
You have the right idea but you're supposed to then subtract $13.75 from the original
So:
55 - 13.75 = $41.25